A novel -mutated human induced pluripotent stem cell model for understanding -mutated tumors - Katsuhito Watanabe; Takashi Nakamura; Shoko Onodera; Akiko Saito; Takahiko Shibahara; Toshifumi Azuma (Tumor Biology)
A missense mutation of the guanine nucleotide binding protein alpha stimulating activity polypeptide 1 ( GNAS ) gene, typically Arg201Cys or Arg201His (R201H/R201C), leads to constitutive activation of the Gsα-cyclic AMP (cAMP) signaling pathway that causes several diseases. However, no germline mutations of GNAS have been identified to date, likely due to their lethality, and no robust human cell models have been generated. Therefore, the aim of this study was to generate GNAS -mutated disease-specific induced pluripotent stem cells as a model for these diseases. We then analyzed the functionality of this induced pluripotent stem cell model and differentiated epithelial cells. We generated disease-specific induced pluripotent stem cells by introducing a mutation in GNAS with the clustered regularly interspaced short palindromic repeats (CRISPR) nickase method, which has lower off-target effects than the conventional CRISPR/Cas9 method. We designed the target vector to contain the R201H mutation in GNAS , which was transfected into human control induced pluripotent stem cells (Nips-B2) by electroporation. We confirmed the establishment of GNAS R201H - mutated ( GNAS R201H/+ ) induced pluripotent stem cells that exhibited a pluripotent stem cell phenotype. We analyzed the effect of the mutation on cAMP production, and further generated teratomas for immunohistochemical analysis of the luminal epithelial structure. GNAS -mutated induced pluripotent stem cells showed significantly higher levels of intracellular cAMP, which remained elevated state for a long time upon hormonal stimulation with parathyroid hormone or adrenocorticotropic hormone. Immunohistochemical analysis revealed that several mucins, including MUC1, 2, and MUC5AC, are expressed in cytokeratin 18 (CK18)-positive epithelial cells. However, we found few CK18-positive cells in mutated induced pluripotent stem cell–derived teratoma tissues, and reduced MUCINs expression in mutated epithelial cells. There was no difference in CDX2 expression; however, mutated epithelial cells were positive for CEA and CA19-9 expression. GNAS R201H -mutated induced pluripotent stem cells and GNAS R201H -mutated epithelial cells have distinct phenotypic and differentiation characteristics. We successfully established GNAS R201H -mutated human induced pluripotent stem cells with increased cAMP production. Considering the differentiation potential of induced pluripotent stem cells, these cells will be useful as a model for elucidating the pathological mechanisms of GNAS -mutated diseases.